Penarapan Metode Quality Control Circle Untuk Mengendalikan Kualitas Produk Reclining Seat Mobil Pada Proses Pengelasan di PT. XYZ - Priyanto, Fiki; Mellyka, Dhea; Tri Pambudi, Andika; Nurjaman, Dede; Catur Kurniawan, Rachman; Kustiwan, Susan (DPPM UNIVERSITAS PELITA BANGSA, 2023)
XYZ is one of the companies that manufacture seat components for four-wheel motor vehicles in Indonesia. The aim of this research is to control and reduce the defect rate in the production of Re-Clean seats. This research uses the Quality Control Circle (QCC) method. With the Quality Control Circle (QCC), we can more easily identify, analyze and solve various work-related problems and apply them in the company's operational activities. The results of this study show that the lack of welding quality is due to the high cycle time of the welding process due to machine factors, method factors and human factors. Of the factors that cause high cycle time problems in the welding process, there is a dominant factor. By looking at the process time of each factor, this makes it easier to overcome problems that are a priority to address. In NG, this happens because the amperage is too high and also the distance between the electrode and the base metal is too far. Over Spatter welding error, meaning spatter is welding spatter, actually if the spatter can be cleaned it is not defective. However, if the amount is excessive and cannot be cleared, it is categorized as a visual impairment. The way to prevent it is to reduce the current as recommended.